A biopsychosocial approach to primary hypothyroidism: treatment and harms data from a randomized controlled trial - Brown, Benjamin T. (Chiropr Man Therap, 2015)
BACKGROUND: Hypothyroidism is a common endocrine condition. There is evidence to suggest that, for a proportion of sufferers, the standard medical treatment does not completely reverse the constitutional and neuropsychiatric symptoms brought about by this condition. The management of hypothyroidism follows a biomedical model with little consideration given to alternative management approaches. There exists anecdotal evidence and case reports supporting the use of a biopsychosocial-based intervention called Neuro-Emotional Technique (NET) for this population. The aim of this study was to explore the potential short-medium term clinical efficacy and safety of NET for individuals with primary hypothyroidism.DesignPlacebo-controlled, blinded, parallel groups, randomized trial. METHODS: Ninety adults with a diagnosis of primary hypothyroidism were recruited from Sydney, Australia. Blinded participants were randomized to either the NET or placebo group and received ten intervention sessions over a six week period. The primary outcome involved the measurement of states of depression using the DASS-42 questionnaire. Secondary outcomes included thyroid function, thyroid autoimmunity testing, SF-36v2 questionnaire, resting heart rate and temperature measurement. Outcomes were obtained at baseline, seven weeks and six months. Questionnaires were completed at the private clinics, and serum measures were obtained and analysed at commercial pathology company locations. Heart rate and temperature were also measured daily by participants. Linear mixed-effects models were used to analyse the continuous outcomes. Unadjusted odds ratios with 95% confidence intervals were calculated for the binary outcomes. RESULTS: Participants were randomly allocated to the NET (n=44) and placebo (n=46) groups. A proportion of the sample displayed neuropsychiatric disturbances and alterations in quality of life measures at baseline. There were no statistically significant or clinically relevant changes in the primary or secondary outcomes between the NET and placebo groups at time seven weeks or six months. There were a few short-lived minor adverse events reported in both the NET and placebo groups that coincided with the application of the intervention. CONCLUSIONS: The application of the NET intervention appears to be safe, but did not confer any clinical benefit to the participants in this study and is unlikely to be of therapeutic use in a hypothyroid population. CLINICAL TRIALS REGISTRATION NUMBER: Australian and New Zealand Clinical Trials Registry Number: 12607000040460.